Efforts to Increase Students' Motivation and Ability in Installing Operating Systems Using the Discovery Learning Model for Class X-TKI Students at SMK Negeri 2 Bandung - Murasadyaufa, Rasyidin (Universitas Pendidikan Indonesia, 2022)
This research aims to determine the increase in student learning motivation and students' ability to install operating systems after implementing a scientific approach with a discovery learning model in Productive Computer Engineering and Informatics subjects in Class X-TKI Students at SMK NEGERI 2 BANDUNG. In carrying out actions in each cycle, we engineer a problem by setting the computer so that it cannot be used because the operating system is damaged. Students are asked to make repairs by reinstalling the operating system. The instruments used were test sheets and observations. The data analysis used was qualitative descriptive analysis. The data analyzed are written and practical test scores on the basic competency